Pengaruh Tingkat Partisipasi Angkatan Kerja dan Upah Minimum Provinsi terhadap Pengangguran di Sumatera Barat - Dini Abdianti; Novera Martilova (Universitas 45 Surabaya, 2024)
This research is motivated by problems with the development of the labor force participation rate and provincial minimum wages which are not in line with the development of unemployment in West Sumatra in 1994-2023. This research aims to find out and analyze how much influence the level of labor force participation and the provincial minimum wage have on unemployment in West Sumatra. This research uses quantitative methods with associative research. The data used is secondary data taken from the West Sumatra Central Statistics Agency (BPS) for 1994-2023. The data collection techniques used were observation and documentation. The data analysis techniques used are classical assumption testing, multiple linear regression analysis, coefficient of determination (R2) testing and hypothesis testing. This research uses SPSS ver. 25 to process data. The research results show that the labor force participation rate variable has a t-count > t-table value (9.113 > 2.052) with a significant value of 0.000 < 0.05, which means that the labor force participation rate has a significant and influential effect on unemployment in West Sumatra. The provincial minimum wage variable has a t-count > t-table value (6.688 > 2.052) with a significant value of 0.000 < 0.05, which means that the provincial minimum wage has a significant influence on unemployment in West Sumatra. Simultaneously, the level of labor force participation and the provincial minimum wage on unemployment in West Sumatra have a value of f-count > f-table (42.123 > 3.340) with a significant value of 0.000 < 0.05, which means that the level of labor force participation and the provincial minimum wage have a significant effect. simultaneous impact on unemployment in West Sumatra.